2006
DOI: 10.1007/s10544-006-6385-7
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid poly(dimethylsiloxane) microsystem for on-chip whole blood filtration optimized for steroid screening

Abstract: Miniaturized biochemical devices in glass, silicon and polymer materials are starting to find their way from the academic laboratories to real-life applications. However, most attention has been given to miniaturize the downstream functions of various microfluidic systems, leaving the sample introduction and preparation steps to more conventional, bulkier solutions. For point-of-care diagnostics in particular, it becomes crucial to be able to handle complex human samples in a miniaturized format.In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 20 publications
0
104
1
Order By: Relevance
“…That device used commercial membranes made of polyethersulfone (PES), polypropylene and polyvinylidene fluoride, cellulose acetate, polycarbonate, and polyvinylpyrrolidone (PVP)/polyethersulfone. 9 Multiple experiments have been conducted on hybrid microfluidic chips to understand how different membranes affect blood plasma extraction. In one study, Wang et al developed a disposable four-layer microfluidic chip to separate blood plasma and viruses from whole human blood.…”
Section: Microfiltration Based On Integrating Filters Within Micromentioning
confidence: 99%
See 3 more Smart Citations
“…That device used commercial membranes made of polyethersulfone (PES), polypropylene and polyvinylidene fluoride, cellulose acetate, polycarbonate, and polyvinylpyrrolidone (PVP)/polyethersulfone. 9 Multiple experiments have been conducted on hybrid microfluidic chips to understand how different membranes affect blood plasma extraction. In one study, Wang et al developed a disposable four-layer microfluidic chip to separate blood plasma and viruses from whole human blood.…”
Section: Microfiltration Based On Integrating Filters Within Micromentioning
confidence: 99%
“…Thorslund et al 9 reported leakage at the interface between the polyvinylpyrrolidone (PVP)/polyethersulfone (PES) membrane and the PDMS substrates. Homsy et al 12 adopted the method of Thorslund et al 9 but changed the substrate material from PDMS to PC and NOA 81 in an attempt to prevent leakage between the two heterogeneous materials. In the current study, we used a two-step injection and curing procedure of UV adhesive to fabricate a fully thermoplastic microfiltration chip for separating blood plasma from human blood, and this chip had ring-shaped structural features on the both poly(methyl methacrylate) (PMMA) substrates around the microchannels and a commercial polycarbonate membrane was sandwiched between the top and bottom substrates.…”
Section: Microfiltration Based On Integrating Filters Within Micromentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous reports have described on-chip plasma separation using microfluidic approaches, such as centrifugation, 24,25 filtration, 26 magnetophoresis, 27 flow bifurcation, 28 and membrane integration. [29][30][31] However, these chips require external power sources or sophisticated fabrication which hinders their widespread application, especially in developing countries. Recently, Dimov et al demonstrated a self-powered, integrated, microfluidic blood analysis system that performed on-chip cell removal and multiple protein binding assays.…”
Section: Introductionmentioning
confidence: 99%